2019
DOI: 10.1177/0734242x19833161
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of municipal solid waste after autoclaving in a passively aerated bioreactor

Abstract: Autoclaving of unsorted municipal solid waste is one of the solutions in waste management that maximises the amount of waste for recycling. After autoclaving, however, a large part of the waste is composed of unstabilised biodegradable fractions (organic remaining fraction, ORF), which may comprise up to 30% of autoclaved waste and cannot be landfilled without further stabilisation. Thus, the aim of this study was to investigate the effectiveness of aerobic stabilisation in a passively aerated reactor of organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Autoclaving is an established industrial-scale process that is widely employed in the waste industry to rapidly, hygienically and effectively recover resources from MSW [71,72]. Compositional profiles for autoclave pre-treated OMSW have been reported in three other studies [10,29,30].…”
Section: Omsw Fibre As a Feedstock For Bio-manufacturingmentioning
confidence: 99%
“…Autoclaving is an established industrial-scale process that is widely employed in the waste industry to rapidly, hygienically and effectively recover resources from MSW [71,72]. Compositional profiles for autoclave pre-treated OMSW have been reported in three other studies [10,29,30].…”
Section: Omsw Fibre As a Feedstock For Bio-manufacturingmentioning
confidence: 99%
“…70% of organic matter, had a high caloric value of 10-12 MJ/kg; AT4 and GP21equaled ca. 25 g O 2 /kg TS and 263 dm 3 /kg TS, respectively [21]. All above values clearly indicate that ORF needs further treatment to reduce its biodegradability.…”
Section: Waste Used In the Experimentsmentioning
confidence: 89%
“…The reactor (with a capacity of 550 L) was equipped with devices for automatic monitoring of temperature and mass. A detailed description of the experimental material and the reactor is presented in Wojnowska-Baryła et al [21].…”
Section: Aerobic Stabilization Of Orfmentioning
confidence: 99%
“…The separated ORF can be also contaminated with glass and other foreign matter, which limits the production of high-quality compost [8]. For this reason, research on the aerobic treatment of the autoclaved organic fraction is being conducted with the goal of achieving aerobic stabilization, i.e., in passive aeration conditions [7]. Another test, performed by Kulikowska et al [9], showed that stabilizate from autoclaved municipal solid waste might be a source of valuable humic substances (HS).…”
Section: Introductionmentioning
confidence: 99%
“…The process of autoclaving disrupts the lignocellulosic structure in organic waste [6], which theoretically facilitates the decomposition of organic matter, both in aerobic and anaerobic conditions. A test performed by Wojnowska-Baryla et al [7] showed that the effect of waste sterilization during autoclaving is not permanent, and the organic remaining fraction converts to biologically unstable material that could not be landfilled without posttreatment (ca. AT4 = 25 g O 2 kg -1 TS).…”
Section: Introductionmentioning
confidence: 99%